Beyond the Shortcut: The Double-Edged Role of AI in Nurturing Creativity and Learning under Pakistan’s Plagiarism Rules - Arshad Mughal, Zanib (JELLL, 2025)
Artificial Intelligence (AI) is rapidly reshaping the way students learn and writers create. In Pakistan, the rise of AI-driven tools such as ChatGPT, Grammarly, and paraphrasing software presents both opportunities and challenges. On one hand, AI supports creativity, enhances writing fluency, and helps learners build confidence. On the other hand, it risks encouraging over-dependence, weakening originality, and clashing with plagiarism policies enforced by the Higher Education Commission (HEC). This paper explores the double-edged role of AI in creative writing and academic learning. It reviews current debates on AI and creativity, analyzes the benefits and drawbacks for students, and examines plagiarism regulations in Pakistan. The study argues that AI should not be treated as a shortcut to success but as a partner in the learning journey. Responsible integration, awareness of plagiarism policies, and fostering human creativity alongside technology are recommended for balanced use.